Denosumab Prevents Early Periprosthetic Bone Loss After Uncemented Total Hip Arthroplasty: Results from a Randomized Placebo‐Controlled Clinical Trial. (4th November 2019) - Nyström, Andreas; Kiritopoulos, Demostenis; Ullmark, Gösta; Sörensen, Jens; Petrén‐Mallmin, Marianne; Milbrink, Jan; Hailer, Nils P; Mallmin, Hans
ABSTRACT: Implant loosening is the most common indication for revision surgery after total hip arthroplasty (THA). Although bone resorption around the implants plays a pivotal role in the pathophysiology of loosening, it is unknown whether potent early inhibition of osteoclasts could mitigate this process and thus reduce the need for revision surgery. We performed a randomized, double‐blind, placebo‐controlled phase 2 trial in 64 patients aged 35 to 65 years with unilateral osteoarthritis of the hip. They underwent surgery with an uncemented THA and were randomized to either two subcutaneous doses of denosumab ( n = 32) or placebo ( n = 32) given 1 to 3 days and 6 months after surgery. Patients were followed for 24 months. Primary outcome was periprosthetic bone mineral density (BMD) of the hip at 12 months as measured by dual‐energy X‐ray absorptiometry (DXA). In addition, [ 18 F] sodium fluoride positron emission tomography/CT (F‐PET) was performed in half of the patients for analysis of periprosthetic standardized uptake value (SUV). Analyses were made according to intention‐to‐treat principles. The trial was registered at ClinicalTrials.gov 2011‐001481‐18, NCT01630941. Denosumab potently inhibited early periprosthetic bone loss. After 12 months, BMD in the denosumab group was 32% (95% confidence interval [CI] 22–44) higher in Gruen zone 7 and 11% (95% CI 8–15) higher in zones 1 to 7. After 24 months, the difference in BMD between groups had decreased to 15% (95% CI 4–27) in zone 7 and 4% (95% CI 0–8) in zones 1 to 7. In both groups, SUV increased after surgery, but the increase was less pronounced in the denosumab group. Biochemical markers of bone metabolism decreased in the denosumab group in the first 12 months, but a rebound effect with marker concentrations above baseline was observed after 24 months. Denosumab potently prevents early periprosthetic bone loss after uncemented THA; however, the effect diminishes after discontinuation of treatment. Further research is needed to determine whether this bone loss will prove to be of clinical importance and, if so, whether the positive effect observed in this study could be preserved by either prolonged treatment with denosumab or additional antiresorptive treatment. © 2019 American Society for Bone and Mineral Research. © 2019 American Society for Bone and Mineral Research.